SENSITIVITY STUDY OF ENVIRONMENTAL FORCES ON JACKET OFFSHORE STRUCTURE - Tuan Mohammad, Tengku Mohd Saifuddin (Universiti Teknologi Petronas, 2008)
This project is sensitivity study of environmental forces on two jacket offshore structure. The main objective of the study is to study the sensitivity of the offshore platforms due to variations in wave, wind, current, earthquake and etc. As a result, several researches have been initiated. This final year project (Thesis) aims to investigate the sensitivity of jacket structures to environmental loadings. In order to perform the research, a real-life jacket structure will be selected and modelled using SACS software package. The sensitivity of jacket structure to variation in design loads will be investigated by performing analysis on main members of this model. For the first semester, sensitivity studies of wave, wind and current have been carried out. Meanwhile, sensitivity studies of earthquake due to the jacket structure can be analyzed. Toward verifying the analysis outcomes and better understanding of the way in which offshore structures react to environmental forces, the sensitivity study of the whole TPDP-A (TOPAZ) platform has been analysed and discussed. Therefore, three (3) different arrangements have been modelled in order to compare with each other arrangements. For this project, environmental forces such as wave played a major influenced in modelling and designing the platform. Designing of the platform should consider the cost and reliability of the model platform. Herewith, capital cost (CAPEX) estimate can be decreased by designing the most suitable jacket platform. Therefore, environmental forces can affect the design of the offshore platform and the author hope that this sensitivity study report of environmental loadings will be a good guideline as compared to the other researchers.